Financial Ratio Analysis on stock prices in hotel, restaurant and tourism sub-sector companies on the Indonesian stock exchange after the COVID-19 pandemic and the new normal - Khairunnida Arief; Arief Hidayat Tumanggor; Iswandi Idris (Jurnal Ekonomi, 2022)
One of the sectors most affected by the Covid-19 pandemic is the tourism sector due to restrictions on human mobility and regional restrictions to avoid the spread of the virus and the biggest impact is experienced by the Hospitality Service Sector. The company's stock price reflects the value of a company. The achievements of the company can be seen from the published financial reports. Financial performance based on financial statements is calculated by a number of financial ratios based on the current ratio, quick ratio, debt to equity ratio, return on equity, return on assets, net profit margin. This makes the financial performance of the hotel, restaurant and tourism sub-sector companies interesting to study as a background for the problem. The purpose of the study was to determine the effect of the financial performance of the hotel, restaurant and tourism sub-sector companies on stock prices listed on the Indonesia Stock Exchange (IDX) after the COVID-19 pandemic and the new normal. Methods: The type of research used is verification with the Explanatory Survey method, the type of data used is secondary data. The data used in this study were obtained from the Indonesia Stock Exchange website in 2022, the first quarter, as well as external data. The type of research data studied is quantitative data. The population used in this research are: 45 users of the Trade, Services & Investment Sector — Restaurant, Hotel & Tourism. By using the purpose sampling method, 31 companies were obtained. Dependent variable: CR, QR, DER, ROE, ROA, NPM, independent variable: stock price. Data analysis methods: Multicollinearity Test, Heteroscedasticity Test, Auto correlation Test, Normality Test. Based on the data analysis that has been carried out, it can be concluded that the debt to Equity ratio (DER) and Return of Equity (ROE) have a separate effect on stock prices, but the current ratio (CR), quick ratio (QR), return on assets (ROA) and net profit margin (NPM) separately have no effect on stock prices